A new species of Brachistosternus Pocock (Scorpiones: Bothriuridae) from southern Peru - Ochoa, José Antonio (2002)
Brachistosternus turpuq, new bothriurid species from the coastal desert of southern Peru is described. It was collected in hills around Mejía (departamento Arequipa). This species belongs to the subgenus Brachistosternus (Leptosternus) Maury, and is related to the Argentinean species B. pentheri Mello-Leitao, B. multidentatus Maury and B. angustimanus Ojanguren Affilastro & Roig Alsina. The new species differs from these species by a lower count of setae on the metasomal segment V and tarsus III, some details of the hemispermatophore (spines of the internal lobe), and the pigmentation pattern of the prosoma and metasomal segment V.